Avaliação da flexibilidade e dor de idosos fisicamente ativos e sedentários - Morcelli, Mary Hellen [UNESP]; Navega, Flávia Roberta Faganello [UNESP]; Navega, Marcelo Tavella [UNESP] (My University, 2010)
Introduction: Among others things, ageing results in neuromuscular decrease. The physical activity practice may to influence positively the ageing process. Objective: To evaluate the flexibility and the level of pain on the sedentary and physically active elderly. Method: Forty-two elderly participated of this study, both male and female, (twenty-two physically active and twenty sedentary), over sixty years old and functionally capable to perform the evaluations suggested. They were submitted to tests of decrease in anterior flexion of the trunk, Stibor and Shoeber to evaluate the flexibility and then they signalized the level of pain on the analogic visual scale. The data obtained on the valuations has been analyzed utilizing the non-parametric statistic test Mann-Whitney, considering the level of significance of 5% (p<0,05), in order to compare the performance among the groups. Results: It has not been observed significant di- fferences among the groups referring to the tests Stibor and analogic visual scale. On Shoeber and FAT tests has been observed significant differences (p<0,05) among the groups, with a better performance to the active group. Conclusion: The physical activity practicing interfere on the mobility and on the flexibility of the elderly body segment.

Introdução: O envelhecimento resulta, entre outras coisas, em decréscimo do sistema neuromuscular. A prática de atividade física pode influenciar positivamente o processo de envelhecimento. Objetivos: Avaliar a flexibilidade e nível de dor de idosos fisicamente ativos e sedentários. Métodos: Foram avaliados 42 idosos de ambos os sexos, acima de 60 anos capacitados funcionalmente para desempenhar as avaliações propostas. Foi formado um grupo de ativos fisicamente com 22 sujeitos (67,41 ± 6,18 anos), e outro grupo de sedentários com 20 sujeitos (68,65±6,19 anos). Os sujeitos foram submetidos aos testes de flexão anterior do tronco (FAT), Stibor e Schoeber para avaliação da flexibilidade e assinalaram o nível de dor na escala visual analógica. Os dados obtidos foram analisados utilizando o teste estatístico não-paramétrico Mann-Whitney. Resultados: Não foram observadas diferenças significativas entre os grupos no que se refere aos testes Stibor e escala visual analógica. Nos testes de Shoeber e FAT, foram observadas diferenças significativas (p<0,05) entre os grupos, com melhor desempenho para o grupo de ativos. Conclusões: A prática de atividade física interfere na mobilidade e na flexibilidade dos segmentos corporais de idosos.
Evaluation of Flexibility and Pain of the Sedentary and Physically Active Elderly
Keywords: idoso; flexibilidade; dor; Atividade Física